Zooplankton in the Schelde estuary (Belgium/The Netherlands). The distribution of Eurytemora affinis: effect of oxygen? - Appeltans, W., A. Hannouti, S. van Damme, K. Soetaert, R. Vanthomme & M. Tackx (Journal of Plankton Research, 2003)
During the 1990s, a spatial shift of the population of Eurytemora affinis (Copepoda, Calanoida) from brackish water towards lower salinities in the Schelde estuary coincided with an increase in oxygen concentration in the freshwater zone. Other ecological and hydrodynamic factors potentially influencing the spatial distribution of the species did not change significantly in either zone, which suggests that the E. affinis population actively responded to the change in oxygen concentration.